Customer returns model in a dual-channel supply chain. (16th November 2015) - Yang, Feng; Hu, Pei; Zhao, Fuguo; Hu, Cuihua
Abstract : Purpose: – The purposes of this paper is to propose a customer returns model in a dual-channel supply chain where a customer can return the purchased product to the retailer or the manufacturer and obtain an equilibrium of selling prices and refund prices and the optimal profit when considering customer returns in the centralized and decentralized dual-channel supply chain. Design/methodology/approach: – This paper mainly uses the game theory technique to analyze the problem. The manufacturer and the retailer are vertically integrated in the traditional channel, and the results of the centralized dual-channel supply chain are obtained. Then, the Stackelberg game was adopted to analyze the decentralized dual-channel supply chain. Finally, the detailed numerical simulation is proposed to obtain straight-forward insights for the industrial managers. Findings: – The mathematic analysis used shows that the main findings of this paper are: in the centralized scenario, the retailer and the manufacturer will charge higher selling prices when they offer return policy, and the demand for each channel increases, which results in higher profit; and the price and refund price of the direct channel in the centralized and decentralized dual-channel are the same, respectively. Originality/value: – Most previous literatures highlight that return policy plays an important role in supply chain which considering one channel. But there is no study on the customer return policy in dual-channel supply chain. This paper is a further step to model the effects of customer returns policy on the pricing policy and optimize the profits in a dual-channel supply chain. This paper analyzes the pricing and refund strategies and gets an equilibrium in the centralized and decentralized dual-channel supply chain scenarios.